Isolasi dan Karakterisasi Minyak Asiri Jeruk Nipis menggunakan GC-MS dan Aktivitasnya terhadap Bakteri Patogen Kulit - Nastiti Nur Indriyani; Adi Susanto (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
In the fruit processing industry, peel is one of the main by-products. Non-edible portions of fruit are likewise seen as waste and are frequently thrown out into the environment. Nowadays, one of the main sources used by the pharmaceutical sector to isolate and extract secondary metabolites is fruit peels. Many applications known for lime peel, especially for antibacterial. This study focuses on the isolation, chemical composition characterization, and antibacterial activity on skin pathogenic bacteria of lime peel essential oil (LPEO). LPEO were isolated using steam distillation and characterized by GC/MS. A total of 24 components were identified. The major constituents of the LPEO were d-limonene (40.24%), β-terpinene (15.68%), sabinene (13.15%), citral (3.41%), α-Terpineol (3.40%), and terpinene-4-ol (2.94%). The antibacterial activity was determined using the Kirby-Baurer method against several bacteria that can cause skin infections. The antibacterial activity of LPEO against Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis dan Propionicbacterium acne is confirmed. LPEO showed varied levels of antibacteria activity against the gram positive and gram negative bacteria. Zone of inhibition (ZOI) in millimetres was used to measure the antibacterial activity, and amoxicillin was used as a control.